2020
DOI: 10.1016/j.mtadv.2019.100026
|View full text |Cite
|
Sign up to set email alerts
|

Time-rate-transformation framework for targeted assembly of short-range attractive colloidal suspensions

Abstract: The aggregation of attractive colloids has been extensively studied from both theoretical and experimental perspectives as the fraction of solid particles is changed, and the range, type and strength of attractive or repulsive forces between particles varies. The resulting gels consisting of disordered assemblies of attractive colloidal particles, have also been investigated with regards to percolation, phase separation, and the mechanical characteristics of the resulting fractal networks.Despite tremendous pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 49 publications
3
30
0
Order By: Relevance
“…By increasing the attraction strength, one can continuously go from a fluid state to a gel state. Another common way to control the gel state consists in playing with the shear history experienced by the system during or after gelation [Ovarlez et al, 2013, Koumakis et al, 2015, Helal et al, 2016, Narayanan et al, 2017, Hipp et al, 2019, Jamali et al, 2020. By tuning the way a colloidal gel is sheared or mixed, one may vary its terminal structure and mechanical strength without changing the Figure 1: Schematic state diagram for colloidal particles with short-range attraction.…”
Section: A Brief Reminder On Colloidal Gelationmentioning
confidence: 99%
“…By increasing the attraction strength, one can continuously go from a fluid state to a gel state. Another common way to control the gel state consists in playing with the shear history experienced by the system during or after gelation [Ovarlez et al, 2013, Koumakis et al, 2015, Helal et al, 2016, Narayanan et al, 2017, Hipp et al, 2019, Jamali et al, 2020. By tuning the way a colloidal gel is sheared or mixed, one may vary its terminal structure and mechanical strength without changing the Figure 1: Schematic state diagram for colloidal particles with short-range attraction.…”
Section: A Brief Reminder On Colloidal Gelationmentioning
confidence: 99%
“…This coupling has been studied within the context of soft glassy rheology 19 21 . Recently, detailed simulations of gelation under flowing conditions have shown that structures that are formed under flow significantly differ from ones that are formed in quiescent conditions, indicating a strong role to be played by the fluid flow in defining the resulting particulate structures 22 . These spatially distributed particle structures exhibit a wide range of exotic rheological responses from an emergence of a yield stress under which the material behaves similar to a viscoelastic solid, to time- and rate-dependent flows that are referred to as thixotropic elasto-visco-plastic (TEVP) 19 , 23 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the micromechanistic view of the physical underpinnings in these complex rheological behavior is essential in controlling the mechanics of colloidal gels. Recent advances in scattering techniques 29 31 as well as detailed computer simulations 22 , 23 , 32 34 have brought an invaluable insight into understanding the evolution of the colloidal structures under different flowing conditions. A focal point of many studies have been the fundamentals of yielding in colloidal gels 35 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thixotropy observed in many complex fluids generally manifests in the sensitivity of the viscosity to the history of the applied strain rate 17 19 . Thixotropic effects originate from evolution of the material’s microstructure as a result of the interplay between shearing forces exerted by the flow and the natural structure formation 20 22 . Thus, in thixotropic constitutive equations, one will critically need to solve for the time evolution of a structure parameter under flow.…”
Section: Introductionmentioning
confidence: 99%